Diagnosis and treatment of pneumonia in children (Texas Journal of Medical Science, 2023)
Early diagnosis and rational therapy pneumonia in children is an urgent task of pediatrics. For diagnosing a bacterial infection, especially a severe one, assessing the appearance and behavior of the child is much more important than reading a thermometer [6,7]. Signs that allow to assess the severity of intoxication, common with a bacterial infection, include a rapid disturbance violation of the general condition, a decrease in the activity of the child; irritability (screaming when touched), lethargy, drowsiness (sleep longer), lack of eye contact of the child during examination, the child refuses to eat and drink. The severity of the condition is determined by the severity of tachycardia, muffled heart sounds, hypo- or hyperventilation, cough, dyspnea, bronchophony and local rales, violation of microcirculation, peripheral cyanosis, incessant vomiting. Amoxicillin is effective against most of the pathogens that cause communityacquired pneumonia. Patients in the presence of underlying diseases or taking antibiotics in the previous 3 months are prescribed amoxicillin / clavulanate in monotherapy or in combination with macrolides (azithromycin, clarithromycin). Macrolides should also be used when mycoplasma or chlamydial pneumonia is suspected